FEATURES OF INFLUENCE OF EMOTIONAL STRESS DURING PREGNANCY ON THE FORMATION OF EATING BEHAVIOR IN THE CHILD - J. R. Gardanova; S. A. Salehov; V. I. Esaulov; D. F. Khritinin; I. I. Abdullin; S. D. Abdyrahmanov; G. A. Galliamova; K. A. Anisimova (Исследования и практика в медицине)
The actuality of the problem of high level of anxiety and the development of psycho-emotional disorders in women during pregnancy currently occupy a leading place in clinical practice. Pregnant "seize" the problem by using a non-adaptive coping and thereby form a similar pattern of behavior in stressful situation and in the fetus, perinatal-formed a similar pattern.Materials and methods. Clinical-descriptive, formulated the concept of the influence psycho-emotional stress and characteristics of the current pregnancy on the background of the formation of patterns of eating behavior in the fetus, followed by implementation after birth under the provisions of the dominant by A. A. Ukhtomsky, the theory of functional systems P. K. Anokhin, the endogeneity of the regularities of pathological processes, the pyramid of needs of A. Maslow.Results. As a result of the establishment of the concept, doctors will be able to identify the maladaptive pattern of eating behavior in pregnant women and to make timely prevention of the formation of this pattern in the fetus.Conclusion. The use of the developed concept could help doctors to identify the maladaptive pattern of eating behavior in pregnant women and make timely prevention of the formation of this pattern in the fetus.